MODIFIKASI TEPUNG WIKAU MAOMBO DAN APLIKASI ISOLAT PROTEIN DAN EKSTRAK ETANOL TAMBELO (Bacthronophorus SP) PADA PRODUK BISKUIT - Wahyuni, Sri; Faradilla, RH Fitri; karim, fahrul (Jurnal Sains dan Teknologi Pangan, 2020)
ABSTRACTThe purpose of this study was to determine the effect of adding protein isolate and tambelo ethanol extract on the organoleptic assessment and nutritional value of Wikau Maombo biscuit products. This study used a two-factor completely randomized design (CRD). T0E0 as a control, T1E1 (isolate 5%, ethanol 0.1%), T1E2 (isolate 5%, ethanol 0.5%) T1E3 (isolate 5%, ethanol 1%), T2E1 (isolate 10%, ethanol 0.1 ) T2E2 (isolate 10%, ethanol 0.5%), T2E3 (isolate 10%, ethanol 1%), T3E1 (isolate 15%, ethanol 0.1%), T3E2 (isolate 15%, ethanol 0.5%), and T3E3 (isolate 15%, ethanol 1%). The results show that the addition of Tambelo protein isolate and Tambelo ethanol extract had a very significant effect on the organoleptic assessment of the color and taste of biscuit products. Meanwhile, the treatment had a significant effect on the assessment variables of aroma, texture, and crispness of biscuit products. The nutritional content of biscuits from modified flour with added protein isolate and Tambelo ethanol extract was better than the control. The results show that the addition of protein isolate and tambelo ethanol extract to the Wikau Maombo biscuit was preferred by panelists and had proximate quality in accordance with the national standards, except for fat and carbohydrate contents.Keywords: wikau maombo, tambelo protein isolate, tambelo ethanol extract, biscuitABSTRAKTujuan penelitian ini untuk mengetahui pengaruh penambahan isolat protein dan ekstrak etanol tambelo terhadap penilaian organoleptik dan nilai gizi produk biskuit wikau maombo. Penelitian ini menggunakan rancangan acak lengkap (RAL) dua faktor. T0E0 sebagai kontrol, T1E1 (Isolat 5%, Etanol 0,1%), T1E2 (Isolat 5%, Etanol 0,5%) T1E3 (Isolat 5%, Etanol 1%), T2E1 (Isolat 10%, Etanol 0,1) T2E2 (Isolat 10%, Etanol 0,5%), T2E3 (Isolat 10%, Etanol 1%), T3E1 (Isolat 15%, Etanol 0,1%), T3E2 (Isolat 15%, Etanol 0,5%), T3E3 (Isolat 15%, Etanol 1%). Hasil penelitian memperlihatkan penambahan isolat protein tambelo dan ekstrak etanol tambelo terhadap penilaian organoleptik berpengaruh sangat nyata terhadap penilaian warna dan rasa produk biskuit. Sedangkan untuk pengaruh penambahan isolat protein tambelo dan ekstrak etanol tambelo pada variabel penilaian aroma, tekstur dan kerenyahan produk biskuit berpengaruh nyata. Kandungan gizi biskuit dari tepung termodifikasi wikau maombo dengan tambahan isolate protein dan ekstrak etanol tambelo lebih baik dibandingkan biskuit tanpa tambahan isolat protein dan ekstrak etanol tambelo. Hasil penelitian memperlihatkan produk biskuit wikau maombo dengan tambahan isolat protein dan ekstrak etanol tambelo lebih disukai oleh panelis dan memiliki mutu proksimat yang sesuai dengan standar SNI, kecuali kadar lemak dan karbohidrat.Key words : wikau maombo, isolat protein tambelo, ekstrak etanol tambelo, biskuit.